We need to solve : "(x^2)y'' - y' - 4(x^3)y = 8(x^3)sin(x^2)"
Substituting "x^2=t \\implies 2xdx=dt"
"\\implies dy\/dx=2xdy\/dt" ---(1)
Differentiating this again, we get;
"d^2y\/dx^2=4xd^2y\/dt^2-(2\/x)(dy\/dt)" ---(2)
Using (1) and (2) in the given equation, we get
"4x^3(y''-y)=8x^3sint"
"\\implies y''-y=2sint"
Solving this, we get;
"(D^2-1)y=2sint"
Complimentary function : "c_1e^t+c_2e^{-t}" (Since, roots of auxiliary equation are 1, -1)
Particular solution : "y=2sint\/(D^2-1)=2sint\/(-(1)^2-1)=-sint"
"=-sint"
Thus, final solution is "y=c_1e^t+c_2e^{-t}-sint"
Substituting "t=x^2" back, we get;
"y=c_1e^{x^2}+c_2e^{-x^2}-sin(x^2)"
Comments
Leave a comment